KEMAMPUAN GURU MATEMATIKA DALAM PENGAJUAN MASALAH - Widayanti, Evi; Ekawati, Rooselyna; Rahaju, Endah Budi (Universitas Insan Budi Utomo, 2025)
This study aims to identify teachers' ability to pose problems. This study uses a descriptive method with a qualitative approach. The data collection methods used are tests, semi-structured interviews, and open interviews. The research subjects were two mathematics teachers at a senior high school. The data were analyzed using the interactive analysis model of Miles, Huberman, and Saldana (2014), which consists of three stages: (1) data condensation; (2) data presentation; and (3) conclusion drawing and verification. The results showed that both subjects posed problems using the pre-solution posing type, which is posing questions based on the given situation or information, and within-solution posing, which is reformulating questions that have already been solved. Neither subject posed problems using the post-solution posing type, which involves modifying the objectives or conditions of a solved problem to create a new problem. In conclusion, teachers' problem-posing abilities showed differences, with ON tending to be limited to pre-solution posing with learning resource constraints, while IM was more varied and coherent. However, both agreed that problem posing is beneficial if supported by appropriate learning strategies and adequate learning resources to encourage student creativity and understanding.